Clinical and urodynamic features of secondary tethered cord syndrome: How can they be found longitudinally?. Issue 1 (16th November 2021) - Lee, Su B.; Im, Young J.; Jung, Jae H.; Do, Minh T.; Lee, Ji Y.; Wang, Kyu‐Chang; Park, Kwanjin
Abstract: Purpose: Secondary tethered cord syndrome (TCS) can be diagnosed with signs of progressive deterioration in urological or neuro‐orthopedic systems following primary untethering surgery. Though urological deterioration is a common secondary TCS manifestation, a paucity of diagnostic criteria makes diagnoses challenging. A detailed description of urological deterioration may help diagnose secondary TCS. Thus, the clinical and urodynamic features of the current secondary TCS cases were described. Materials and Methods: Fifty‐one patients who had undergone reuntethering for secondary TCS experienced improvement or stabilization of progressive problems. Moreover, their clinical and videourodynamic changes were longitudinally described. Results: Loss of postoperative spontaneous voiding was the first urological secondary TCS sign for those who could void spontaneously. Urological problems mostly occurred during elementary school (6–12 years). Major urological presentations were recalcitrant urinary tract infection or urinary incontinence. Follow‐up videourodynamic studies revealed typical changes, from acontractile bladder to overactive and low‐complaint bladders. While detrusor overactivity did not always occur during the progression, detrusor sphincter dyssynergia was always present in all patients with urological deterioration. All patients postoperatively showed significant urodynamic improvement regardless of preoperative bladder dysfunction. This included four cases of restoring spontaneous voiding. Nine patients experienced newly appearing nonprogressive neuro‐orthopedic complications despite their urological improvement. Conclusions: Urological deterioration should prompt secondary TCS suspicion, and changes in clinical patterns and videourodynamic studies helped diagnose it. However, reuntethering can effectively address urological problems at the cost of some neuro‐orthopedic functions in some patients.